Patent ductus arteriosus: The physiology of transition. Issue 4 (August 2018) - Deshpande, Poorva; Baczynski, Michelle; McNamara, Patrick J.; Jain, Amish
Abstract: The transition from intrauterine to extrauterine life represents a critical phase of physiological adaptation which impacts many organ systems, most notably the heart and the lungs. The majority of term neonates complete this transition without complications; however, dysregulation of normal postnatal adaptation may lead to acute cardiopulmonary instability, necessitating advanced intensive care support. Although not as well appreciated as changes in vascular resistances, the shunt across the DA plays a crucial physiologic role in the adaptive processes related to normal transitional circulation. Further, we describe key differences in the behavior of the ductal shunt during transition in preterm neonates and we postulate mechanisms through which the DA may modulate major hemodynamic complications during this vulnerable period. Finally, we describe the conditions in which preservation of ductal patency is a desired clinical goal and we discuss clinical factors that may determine adequate balance between pulmonary and systemic circulation.